IMPLEMENTASI METODE PEMBELAJARAN VARIATIF OLEH MAHASISWA PLP PADA PEMBELAJARAN TEKS NARATIF BAHASA INDONESIA DI KELAS V SDN 007 LONG MESANGAT - Nurngaini; Dina Maryana; Azamul Fadly Noor Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the continued dominance of lecture and question-and-answer methods in Indonesian language instruction at the elementary school level, which causes students to tend to be passive, unfocused, and easily bored during the learning process. This study aims to describe the implementation of varied learning methods carried out by students of the School Field Introduction Program (PLP) in teaching Indonesian narrative texts in the fifth grade at SDN 007 Long Mesangat. This study uses a qualitative approach with a descriptive research design. The research subjects consisted of PLP students, mentor teachers, and fifth-grade students. Data collection techniques included observation, interviews, and documentation. Data analysis utilized the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that varied learning methods were implemented through role-playing, the talking stick method, the snakes and ladders game, interactive games, and the use of audiovisual media. The application of this method creates a learning environment that is more active, interactive, and enjoyable than conventional teaching. Students appear more enthusiastic about participating in lessons, are more confident speaking in front of the class, actively ask and answer questions, and demonstrate greater engagement in learning activities. Thus, the implementation of varied learning methods by PLP students has a positive impact on student engagement, interest in learning, and the quality of learning regarding Indonesian Narrative Texts in Grade 5 at SDN 007 Long Mesangat.